Mobility Index Towards Heritage Tourism Area, Case Study: Borobudur, Prambanan, And Ratu Boko - Pungki Aji, Kurniawan; Kusuma, Andyka; Prih Raharjo, Efendhi (UI Scholars Hub, 2024)
Mobility has become a crucial factor in transportation management, especially in the tourism sector. It is a key indicator of the performance of transportation infrastructure and people's response to it. To evaluate mobility in tourist areas, there is a need for tools to represent its value. In this study, the concept of an index as a measure of performance is applied, gathering information into a simpler and more mutually agreeable form. The cultural heritage sites of Borobudur, Prambanan, and Ratu Boko are chosen as an ideal study location due to their popularity internationally. Given the limitations of previous research on mobility indexes in tourist areas, the Sustainable Urban Mobility Index (I_SUM) framework is used to develop the variables. To avoid bias, this study utilizes expert opinion methods to assess necessary and unnecessary variables in achieving the index. Eight individuals with expertise and experience in transportation and tourism are selected as respondents. Furthermore, the expert evaluation results are processed using the Content Validity Index (CVI). The outcome is 26 variables that meet the validation test out of a total of 32 previous variables, which are divided into five domains, covering accessibility, social aspects, transportation infrastructure, traffic cycle, and transportation systems.